Система раннього попередження та реагування як засіб забезпечення стійкості підприємства - Сітак, Ірина Леонідівна; Мурашко, Ірина Миколаївна (My University, 2019)
У статті розглянуто сутність, місце й роль системи раннього попередження та реагування для забезпечення стійкості підприємства шляхом виявлення кризових умов та недопущення його банкрутства. Система попередження та система управління є складовими частинами будь-якого менеджменту у кризовій ситуації. Першочерговим завданням СРПР є своєчасне виявлення ознак кризи на підприємстві, тобто прогнозування можливого банкрутства. Система попередження забезпечує більш швидку реакцію на початку кризової ситуації (фіксуються несприятливі зміни, поширюється інформація про них); як персональний захист, так і захист активів; активізацію системи реагування. За допомогою системи раннього попередження та реагування виявляються можливості забезпечення стійкості підприємства або додаткові шанси для суб’єкта господарювання. Розроблення, формування та впровадження на підприємстві системи раннього попередження й прогнозування є необхідним заходами для успішного та стабільного розвитку й функціонування будь-якого суб’єкта господарювання в сучасних умовах розвитку економіки.

The authors of the article have disclosed the essence of early warning and response system. The article discusses the essence, place and role of the early warning and response system to ensure the sustainability of the enterprise by identifying crisis conditions and preventing and preventing its bankruptcy. Warning system and control system is an integral part of any management in a crisis situation. The primary task of the early warning and response system is the timely identification of signs of a crisis in the enterprise, that is, the prediction of possible bankruptcy. The warning system provides: faster response at the beginning of a crisis situation (unfavorable changes are recorded and information about them is disseminated); protection of both personal and asset protection; activation of the response system. With the help of an early warning and response system, opportunities to ensure the sustainability of the enterprise or additional opportunities for the enterprise are identified. The development, formation and implementation of an early warning and response system at an enterprise is an objective necessity for the successful and stable development and functioning of any enterprise in modern conditions of economic development. Taking into account the features of the system of early warning and response, in accordance with the requirements of the situational approach, it is advisable to build on the principles of system, expediency, objectivity, realism, concreteness, timeliness, and efficiency. The introduction of a balanced scorecard in enterprises allows you to monitor the implementation of the strategy in real time and make timely adjustments to them taking into account internal changes and the impact of the external environment. The use of a balanced scorecard eliminates strategic management conflicts that may arise between the owners themselves and hired top managers. The controlling department is always responsible for building a balanced scorecard at the enterprise. This is explained by the fact that a balanced scorecard is an addition to the controlling tools. The proposed Society block provides for the management of the social component of the enterprise in accordance with certain criteria, and allows for timely adjusting the strategy of the enterprise in the absence of personnel resistance.
Early warning and reaction system as a means of ensuring the sustainability of the enterprise
Keywords: управління підприємством; економічна стійкість; стратегічне управління; management; economic stability; strategic management